Sports finance - Brian P. Soebbing (MDPI, 2018)
The use of sport as an empirical setting to study different organizational and economic phenomena is continuously increasing (Day et al., 2012; Kahn, 2000; Wolfe et al., 2005). Specifically, in the finance literature, sports have been used to examine market efficiency (e.g., Edmans et al., 2007; Golec & Tamarkin, 1991; Gray & Gray, 1997, Woodland & Woodland, 1997), the financing of sports facilities (Baade & Matheson, 2006; Coates & Humphreys, 2003; Rebeggiani, 2006), and mega events (Madden, 2006).In addition, sports have many unique qualities, which contribute to an industry generating revenues estimated between 44 and 60 billion dollars in the United States (Humphreys & Ruseski, 2009). The study of sports has emerged both as an academic major and as a field of research, with sports financing being one of the main areas of scholarship in the field of research. Thus, the primary goal of this Special Issue will highlight sports' activities as an empirical setting for understanding financial phenomena and will highlight sports' unique financial idiosyncratic characteristics. Topics in this Special Issue can include, but are not limited to, non-profit sports clubs, mega events, financial issues related to stadiums and arenas, amateur and professional sports leagues and teams, and gambling markets, including sports betting, lotteries, and other games of chance.
Keywords: 330